Penerapan model Problem Based Learning untuk meningkatkan Berpikir Kritis siswa Sekolah Dasar; Studi Literatur - Nisa, Sofi Chairun; Rigianti, Henry Adiitia (Universitas Muhammadiyah Magelang, 2025)
This study aims to apply the Problem-Based Learning (PBL) model in improving critical thinking skills of elementary school students through literature studies. PBL is a learning approach that encourages students to be active in solving contextual problems in order to hone high-level thinking skills. This study examines a number of relevant scientific sources from the last ten years. The results of the analysis show that the PBL model is effective in improving critical thinking skills, such as the skills of analyzing, disseminating, and drawing logical conclusions. In addition, collaborative learning in PBL also strengthens students' communication skills and responsibilities in the learning process. Thus, it can be concluded that PBL is an appropriate learning strategy to develop critical thinking skills at the elementary school level, as long as it is supported by teacher training and good planning.